Case Report: Skeletal and cardiovascular alterations compatible with a connective tissue disorder in an elderly dog - Bilgiç, Bengü; Koenhemsi, Lora; Pugliese, Michela; Altındal, Abdullah; Or, Mehmet Erman (Frontiers in Veterinary Science, 2025)
A 15-year-old intact female Siberian Husky was referred for hindlimb paresis, anorexia, and cachexia. Cardiac auscultation revealed a grade 5/6 systolic murmur, with maximum intensity over the right hemithorax. Right lateral thoracic radiography revealed an undulating thoracic aorta with a normal vertebral heart scale. The patient had a left-sided scoliosis deformity at the lower thoracic and upper lumbar levels. In addition, sternum deformity revealed pectus excavatum, with no history of trauma in the anamnesis. Echocardiographic examination revealed aortic regurgitation (5.29 m/sn) and dilation of the aortic root and proximal ascending aorta in the parasternal long-axis view. The left ventricle was mildly enlarged, and the left atrial diameter was within reference ranges. This case describes an uncommon combination of skeletal and cardiovascular abnormalities in an elderly dog, raising the suspicion of a connective tissue disorder. However, in the absence of molecular or histopathological confirmation, the diagnosis remains presumptive. The case highlights the need for further genetic investigations and the establishment of specific diagnostic criteria for connective tissue fragility syndromes in veterinary medicine.